Post-Modernism and Neoliberalism: Two Ideological and Political Facets of a Supposedly New Era - Carcanholo, Marcelo Dias; Baruco, Grasiela Cristina da Cunha (Pontifícia Universidade Católica de São Paulo, 2009)
This article seeks to criticize post-modern thought with regard to some of its major categories, such as the post-industrial and post-class society, based on Marx’s analysis of the operation of the capitalist mode of production. The goal is to show how the thought, discourse and political practice of post-modernism are appropriate to both this specific historical stage, represented by neoliberalism, and the content of capitalism itself. The conclusion is that, as a result, post-modernism, even when it tries to be critical, is not a theoretical or political alternative to capitalism.